Characterization of the Gut Microbiota of Mackerel Icefish, Champsocephalus gunnari - Hokyung Song; Seungyeon Lee; Dong-Won Han; Jin-Hyoung Kim (Fishes, 2022)
The gut microbiome of Antarctic fish species has rarely been studied due to difficulties in obtaining samples. The mackerel icefish, Champsocephalus gunnari, primary feeds on krill and is one of the key species in the food web of the Southern Ocean. In this study, we characterized the gut microbiota of C. gunnari by sequencing the V3–V4 region of the bacterial 16S rRNA gene based on the Illumina MiSeq sequencing platform. We collected three types of samples: (1) whole intestine, (2) intestinal wall, and (3) intestinal content. The results showed no significant difference in the alpha diversity between different sample types. However, the microbial community composition of intestinal wall samples was distinct from other sample types. The relative abundance of Photobacterium was higher in intestinal content compared with the walls, which could be due to their chitinolytic activity. In contrast, potential pathogens such as Escherichia, Shigella, and Pseudomonas relatively more abundant in the intestinal wall compared with the intestinal contents. Unlike the gut microbiome of other marine fish species, Vibrio and Lactobacillus were nearly absent in the gut microbiome of C. gunnari. Functional gene profile of the gut microbiome predicted by PICRUSt2 showed higher relative abundance of genes related to biodegradation of nutrients in intestinal content. In contrast, the relative abundance of genes related to biosynthesis of important metabolites, such as menaquinols, was higher in intestinal wall. The difference in the microbial community structure of intestinal wall and intestinal content found in our study supports niche separation in the gut environment and emphasizes the importance of collecting intestinal wall samples in addition to intestinal content samples to understand the full picture of gut microbiome. This is the first time that the gut microbiome of mackerel icefish has been characterized using next-generation sequencing.